Prospects of library use data integration in campus information systems: A glocalized perspective - Sant-Geronikolou, Stavroula; Martinez-Avila, Daniel [UNESP] (Epi, 2019)
The study seeks to investigate the stakeholders' perceptions of organizational forces and operational issues that weigh upon the academic library's data capabilities, with a special focus on the Greek academic librarians' appreciation of the prospects of library use data integration in campus information systems. Findings from online interviews with international learning analytics experts and Greek academic library directors, that aimed to record their viewpoints around difficulties of integrating library data into learning analytics systems, brought to light several interpretative, organizational culture, librarian professional development, and user buy-in concerns. Interviewees made several recommendations related to collective action, training, and communications also stressing the importance of institutional support and active involvement of professional associations. The analysis of the participants' perspective provides a solid conceptual foundation for interpreting local issues associated with library use data capitalization within and beyond intra-institutional initiatives in the overarching goal to contribute actionable data to the development of context-specific tailor-made solutions.
Keywords: Academic libraries; Data; Library use; Learning analytics; Higher education; University; Metrics; Perceptions; Campus information systems; Organizational culture; Professional development; Prospects; Recommendations; Solutions; Greece